Phytohormone Priming of Tomato Plants Evoke Differential Behavior in Rhizoctonia solani During Infection, With Salicylate Priming Imparting Greater Tolerance Than Jasmonate - Koley, Paulami; Brahmachari, Subhadip; Saha, Amitava; Deb, Camelia; Mondal, Monimala; Das, Nebedita; Das, Arpan; Lahiri, Suvanwita; Das, Mayukh; Thakur, Manisha; Kundu, Surekha (Frontiers in Plant Science, 2022)
ABSTRACT : In the field of phytohormone defense, the general perception is that salicylate (SA) mediated defence is induced against biotrophic pathogens while jasmonate (JA) mediated defense functions against necrotrophic pathogens. Our goals were to observe the behaviour of the necrotrophic pathogen Rhizoctonia solani in the vicinity, on the surface and within the host tissue after priming the host with SA or JA and also to see if priming with these phytohormones would affect the host defense differently upon infection. It was observed for the first time, that R. solani could not only distinguish between JA versus SA primed tomato plants from a distance, but surprisingly avoided SA primed plants more than JA primed plants. To corroborate these findings, early infection events were monitored and compared through microscopy, Scanning Electron Microscopy and also Confocal Laser Scanning Microscopy using transformed R. solani expressing green fluorescence protein gene (gfp). Different histochemical and physiological parameters were compared between the unprimed control, JA primed and SA primed plants after infection. The expression of a total of fifteen genes, including appressoria related gene of the pathogen and twelve marker genes functioning in the SA and JA signaling pathways were monitored over a time course during early infection stages. R. solani being traditionally designated as a necrotroph, the major unexpected observations were that Salicylate priming offered better tolerance to R. solani than Jasmonate priming and that it was mediated through the activation of SA-mediated defense during the initial phase of infection, followed by JA-mediated defense in the later phase. Hence, the present scenario of biphasic SA-JA defense cascades during R. solani infection, with SA priming imparting maximum tolerance, indicate a possible hemibiotrophic pathosystem that needs to be investigated further.